2016
DOI: 10.1002/sdtp.10780
|View full text |Cite
|
Sign up to set email alerts
|

52-2:Invited Paper: OLED Microdisplays - Enabling Advanced Near-to-Eye Displays, Sensors, and Beyond

Abstract: OLED-on-Silicon technology has become vital to emissive microdisplays in near-to-eye displays, e.g., upcoming smart glasses. High-resolution OLED micro-patterning, embedded sensors and emission spectra outside the visible enable advanced features. Low-power active-matrix circuitry CMOS backplane architecture broadens the application range. Recent developments will be reported here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…The TE-type NIR-OLED structure is well suited for integration with a CMOS-based high-definition backplane formed on a silicon substrate ( 21 23 ). With such a combination, active scanning of fine NIR-OLED pixels becomes possible.…”
Section: Resultsmentioning
confidence: 99%
“…The TE-type NIR-OLED structure is well suited for integration with a CMOS-based high-definition backplane formed on a silicon substrate ( 21 23 ). With such a combination, active scanning of fine NIR-OLED pixels becomes possible.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a visual system that uses a curved microdisplay can reduce the system volume by 29.1% compared to a system that uses a flat microdisplay [53]. Fraunhofer Institute reported image sensor-integrated OLED microdisplays in 2009 [54][55][56][57][58][59]. As shown in Figure 8(c), the RGBW light emitters and photodetector were arranged in the same panel, displaying images and detecting light simultaneously.…”
Section: High-performance Oled Microdisplays For Small-form-factor Ar Devicesmentioning
confidence: 99%
“…In such applications, the microdisplay may not need to be full-color and highresolution and to have a high frame rate but may need to be small and with low power consumption. Vogel et al reported an ultra-low-power OLED microdisplay for wearable visualization [58][59][60]. A highly efficient green monochrome OLED device was designed and fabricated, which resulted in a maximum current efficiency of 47.7 cd/A at 1,000 cd/m 2 .…”
Section: High-performance Oled Microdisplays For Small-form-factor Ar Devicesmentioning
confidence: 99%
“…Similar approaches are needed in the display industry. Currently, battery life in mobile devices is dominated by the active-matrix organic light-emitting diode (AMOLED) display; over half of the battery energy is either consumed by the display backplane 7 or lost due to battery voltage upconversion to the necessary supply voltages of the system. 8 The high leakage current of lowtemperature polycrystalline silicon (LTPS) thin-film transistors (TFTs) and the relatively low field-effect mobility of indium gallium zinc oxide (IGZO) TFTs at present eliminate both as stand-alone solutions for variable image refresh rate display backplanes, where as low as 0.1 Hz of refresh rate is desired for "still" images and up to 240 Hz for dynamic images.…”
Section: Introductionmentioning
confidence: 99%